Voluntary Tax Compliance and Small and Medium Enterprises (SMEs) in Jos Metropolis - O. Gbegi, Daniel; Alexander, Duah; Ibrahim , Uthman; Lass, Ruth (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Small and Medium Enterprises (SMEs), like every other businesses, are not exempted from payment of taxes. Any registered business whether SME or not are expected to remit one form of tax or another levy to the relevant statutory body upon registration. This study investigated voluntary tax compliance by small-and medium-sized enterprises (SMEs) in Jos Metropolis. The study examined the extent that tax knowledge, ethical attitudes, role of tax authority and ownership challenges relate with voluntary tax compliance. Data were collected through a researcher–administered questionnaire survey conducted in Jos using 85 respondents being the population of small business taxpayers registered with Plateau Board of Internal Revenue (PBIR). Data was presented and analyzed using Descriptive Statistics and Pearson Correlation Coefficient with the help of SPSS version 23.0. The results revealed that tax knowledge has a positive moderate relationship with voluntary tax compliance, and business ownership structure has a strong positive significant relationship with voluntary tax compliance, while the role of tax authority has a weak positive relationship with voluntary tax compliance. Also, the study revealed that ethical attitudes has a weak negative relationship with voluntary tax compliance. The implication is that among the factors, aside audit and penalty and coercive methods, tax knowledge can positively influence voluntary tax compliance. It was recommended that policy makers should embark on continuous enlightenment and awareness campaign to educate SMEs in Jos of their social responsibility to pay tax and give them information about tax procedures. It was further recommended that government should improve on quality of public governance to win the confidence and trust of taxpayers